Pandemic recessions and contact tracing - Leonardo Melosi; Matthias Rottner (Deutsche Bundesbank, 2021)
We study contact tracing in a new macro-epidemiological model in which infected agents may not show any symptoms of the disease and the availability of tests to detect asymptomatic spreaders is limited. Contact tracing is a testing strategy that aims to reconstruct the infection chain of newly symptomatic agents. We show that contact tracing may be insufficient to stem the spread of infections because agents fail to internalize that their individual consumption and labor decisions increase the number of traceable contacts to be tested in the future. Complementing contact tracing with a timely, moderate lockdown corrects this externality, allowing policymakers to buy time to expand the testing scale so as to preserve the testing system. If the testing capacity is sufficiently large, contact tracing alone can halt the spread of the virus because it allows policymakers to allocate tests along the reconstructed infection chains. We provide theoretical underpinnings to the risk of becoming infected in macro-epidemiological models. Our methodology to reconstruct infection chains is not affected by curse-of-dimensionality problems.
Keywords: E10; D62; I10; 330; Contact tracing; testing; quarantine; externality; infection chain; lockdown; epidemics; SIR-macro model; COVID-19